"Complexity, safety and challenges: Emergency responders' experience of people affected by methamphetamines". (8th August 2022) - Jones, Rikki; Jackson, Debra; Woods, Cindy; Usher, Kim
Abstract: Providing care to methamphetamine‐related callout events in the prehospital environment is often complex and resource‐intensive, requiring staff to manage agitation and violence‐related side effects of methamphetamines. In Australia, emergency responders are increasingly required to attend events related to methamphetamines, even though reports suggest methamphetamine use across Australia has declined. The aim of the study was to explore Australian police and paramedic experiences attending methamphetamine‐related events. A qualitative descriptive phenomenology design was employed using semi‐structured interviews with employed police (10) and paramedics (8) from Australia. Data were analyzed using thematic analysis. Participants described the complexities associated with providing prehospital care to people affected by methamphetamines. Participants described associated domestic/family violence, increased levels of violence, challenges with communication, and responder emotional and psychological distress and physical injury. Violence associated with methamphetamine use is a critical factor in prehospital care. Workplace violence and family/domestic violence are important issues that require further research to ensure families and staff are well supported and have the services they need to continue responding to people affected by methamphetamine use.